PERAHU-PERAHU MASA KLASIK, BUKTI KEJAYAAN NEGERI BAHARI INDONESIA - Hari Lelono (Berkala Arkeologi, 2009)
The Honor of our Nation is often tested by our neighbouring countries with some provocative actions. Since the ancient period of Majapahit Kingdom which was also well-known as a maritime kingdom, Gajah Mada had succeeded in uniting the Nusantara (the Nation) through his strong military navy. It’s neither a myth nor a slogan because it has been proven archaeologically by the ships reliefs sculptured on the wall of the Borobudur Temple dated back to 200 years ago. Other evidence is on the inscriptions of Kediri and Majapahit which mentioned about ships, fishermen, captain and the process of building a ship. The spirit as well as the intelligence of our ancestors must be appreciated and honored as a real breath and spirit of our own, presenting an identity and dignity of one Nation. This pride will be the most precious base maintain the unition of Negara Kesatuan Republik Indonesia.